Patrimônio sustentável: reflexões sobre as melhores práticas anglo-saxônicas aplicadas a edificações culturais - Anna Sophia Barbosa Baracho (2013)
This masters thesis have the aim to investigate the construction of the Sustainable Heritage concept through studies case, based on best practices, standards and benchmarks developed and published from the experiences of some Anglo-Saxon countries belonging to the UK, North America and Oceania. Search to contribute with the various professionals who examine issues of sustainability and preservation of cultural heritage, especially those embodied in the buildings transformed into museological spaces. Previous readings showed that throughout history, heritage and sustainability walked through parallel pathways, however, in the early years of the twenty-first century, appeared the need to identify and strengthen the significance that heritage have in different scales wherein the cultural goods have not only historical and/or artistic values but also economic and environmental importance: preserve with responsible attitudes not only from a cultural standpoint, but also social, economic, with respect to the environment and without damaging their true values, to the community and the engines of development. These approaches must be integrated into a strategy for sustainable management of existing buildings, to the extent that enable adaptation to current needs. Firstly, the term "Sustainable Heritage" or the binomial sustainability-heritage, is discussed, and finally, from the study of the treatment of museum spaces, identify the main requirements to assist in developing a sustainability checklist, consisting by structured tables with socioeconomic, sociocultural and environmental approaches. Each of these tables serves as the basis of the beginning of a long process that is the sustainable development and construction of sustainable heritage with practical applicability in museums. The objective is to seek solutions and goals to assist in choosing the installation of a museum and its collections and to attend in making decisions that conducts the management of installed museological spaces in historic buildings. The conclusions indicate to the feasibility of implementing these alternatives to studies of sustainable heritage, understanding the significance of the historic buildings, its architectural features and its contributions to the community, including its context and its setting, ensuring that the information is sufficient to correctly understand the possible impact of intervention on the well-built.